Examining factors influence the morality of secondary school students in South-Western Nigeria - Muhammed-Lawal, Adam Adesina
This study was conducted with manifold objectives, the most important being to examine the level of Nigerian secondary school students' adherence to the practice of Islamic moral teaching guides, school culture, family and Internet influences and their effect on morality; to establish whether statistically significant differences exist between the type of school, gender, level of study and age in terms of students' morality; to explore the statistically significant relationship between morality and Islamic Guidance, School Culture, Family and Internet Influences; and to identify the strongest statistically significant predictor(s) of students' morality. Therefore, a quantitative survey design was employed on a total sample of 365 respondents among secondary school students in the geo-political zone of south-western Nigeria. The tool used for data collection was a questionnaire, of which the proportional stratified random sampling was utilized as the sample technique procedure. The questionnaire scale contained 63 items rated on a 5-point Likert scale. The questionnaire was developed based on extracted literature and content validated by 7 experts in the fields of Islamic Education, Research Methodology and Applied Statistics. The data were analyzed using Descriptive Statistics, Principal Component Analysis (PCA), Independent sample t-test, Pearson Product Moment correlation (PPM) analysis as well as Multiple Regression Analysis (MRA). SPSS version 22 was employed for the analysis of data. The results indicated that the majority of secondary school students were morally imbibed in their behavior with an average percentage of 77.4% in the morality dimension, 92.2% for Islamic guidance, 91% for school culture, 90% for family influence and 88% for Internet influence. Furthermore, the results of T-test show that there is no statistically significant difference in the type of school, gender, level of study and age towards morality. However, there is a statistically significant relationship between Islamic guidance, school culture, family influence, internet influence towards morality. Islamic Guidance (IG) and school culture (SC) are significant predictors of students' morality. Based on the findings of this study, the researcher recommends that curriculum experts and designers need to engage themselves in developing a sound moral education curriculum for all levels of Nigerian secondary schools that will reflect an expected level of morality in the Nigerian society, which includes honesty, tolerance, obedience, truthfulness, love, patriotism and peaceful coexistence.